Muslim scholars and the world of social media: opportunities and challenges - Sule, Muhammad Maga; Abdulkareem, Lawal (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2020)
The paper has examines what is considered dual contributions of the internet based medium of communication in Da’wah. These platforms for social interaction and communication have become medium of spreading Islamic messages by Islamic scholars. The objective of the paper is to analyze how internet related mane of communications and interaction have aided Da’wah. The researchers adopted an explanatory type of research whose aim is to explain a phenomenon of choice. The researchers sourced data from the secondary sources and analyzed them. It is on the basis of such that, the findings of this research have portrayed that social media as medium of social interaction have been adopted as tools for Da’wah which learned Islamic scholars are using to propagate Islam and its teachings. However, the outcomes confirmed that social media have provided a fruitful ground for the germination of cyber space Islamic scholars, people who are not learned but share texts, video and audio containing distorted and misleading information. This has challenged the age long Islamic practice in Islam where any issues regarding Islamic Da’wah and Fatwa are exclusively for the learned Islamic Scholars. The study in addition reveal that what is obtainable on the social media now is, cyber scholars and quick to post or comment on issues that are exclusive the purview of Islamic scholars.